“3Co principle” for fidelity assessment for bulb flat models in ship structural analysis. - Shi Song; Sören Ehlers; Moritz Braun; Franz von Bock und Polach; Aditya Rio Prabowo (Results in Engineering)
Although bulb flats have been numerically modelled in many ship structural analysis, whether a bulb flat model should be accepted and applied is seldom discussed. Thus, it is worthwhile to investigate the evaluation of numerical models, which can be accomplished by fidelity assessment. However, there has been no systematic fidelity assessment for bulb flat models. This is due to the absence of sufficient information or assessment strategy. To enable this, in this study, a “3Co principle” is introduced as a framework for the fidelity assessment. Moreover, two bulb flat models, namely the shell-only model and the beam & shell model, are fully described with their relevant data. Following this, the fidelities of these two models are gradually examined using the 3Co principle. It is revealed in this study that, the fidelity of bulb flat model can be systematically assessed via the 3Co principle, together with sufficient information. The results of the presented research are believed to provide a sound basis for the use of bulb flat models in future applications regarding non-linear ship structural analysis.